A Distributed Algorithm for Identifying Strongly Connected Components on Incremental Graphs - Srinivasan, S.; Khanda, A.; Srinivasan, S.; Pandey, A.; Das, S. K.; Bhowmick, S.; Norris, B. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2023)
Incremental graphs that change over time capture the changing relationships of different entities. Given that many real-world networks are extremely large, it is often necessary to partition the network over many distributed systems and solve a complex graph problem over the partitioned network. This paper presents a distributed algorithm for identifying strongly connected components (SCC) on incremental graphs. We propose a two-phase asynchronous algorithm that involves storing the intermediate results between each iteration of dynamic updates in a novel meta-graph storage format for efficient recomputation of the SCC for successive iterations. To the best of our knowledge, this is the first attempt at identifying SCC for incremental graphs across distributed compute nodes. Our experimental analysis on real and synthesized graphs shows up to 2.8x performance improvement over the state-of-the-art by reducing the overall memory utilized and improving the communication bandwidth.